2017
DOI: 10.1097/j.pain.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Gene-to-gene interactions regulate endogenous pain modulation in fibromyalgia patients and healthy controls—antagonistic effects between opioid and serotonin-related genes

Abstract: Chronic pain is associated with dysfunctional endogenous pain modulation, involving both central opioid and serotonergic (5-HT) signaling. Fibromyalgia (FM) is a chronic pain syndrome, characterized by widespread musculoskeletal pain and reduced exercise-induced hypoalgesia (EIH). In this study, we assessed the effects of 3 functional genetic polymorphisms on EIH in 130 patients with FM and 132 healthy controls. Subjects were genotyped regarding the mu-opioid receptor (OPRM1) gene (rs1799971), the serotonin tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 42 publications
5
58
1
4
Order By: Relevance
“…Furthermore, patients with FM showed hyperalgesia and no activation of pain-inhibitory mechanisms, segmental or plurisegmental, during static muscle contractions. Rather, an increase in pain sensitivity was seen [ 10 , 13 ]. Patients with shoulder myalgia showed an activation of the pain-inhibitory mechanisms when contracting a non-painful muscle distant to the pain but a lack of activation when contracting the painful muscle [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, patients with FM showed hyperalgesia and no activation of pain-inhibitory mechanisms, segmental or plurisegmental, during static muscle contractions. Rather, an increase in pain sensitivity was seen [ 10 , 13 ]. Patients with shoulder myalgia showed an activation of the pain-inhibitory mechanisms when contracting a non-painful muscle distant to the pain but a lack of activation when contracting the painful muscle [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a genetic association study in humans showed that genetically inferred increased opioid signalling in combination with decreased serotonergic signalling produced better EIH in HC as well as in patients with fibromyalgia (FM). The study revealed antagonistic interactions between opioid and serotonergic signalling upon EIH [ 10 ]. On a behaviour level, exercise activates pain-inhibitory mechanisms in healthy persons with subsequent increase of pain thresholds during muscle contraction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC6A4 encodes the membrane protein responsible for transporting serotonin from synaptic spaces to pre-synaptic neurons. It has been studied for its role in depression-susceptibility in people experiencing emotional trauma [5]. The protein encoded by the FKBP5 gene is a member of the immunophilin protein family.…”
mentioning
confidence: 99%
“…This family of proteins is heavily involved in regulating the immune system, as well as playing a role in basic cellular processes such as protein folding and trafficking [6]. The OPRM1 gene makes a protein known as the mu (µ) opioid receptor, which is important for regulating reward, pain, and addictive behaviours in our bodys opioid system [5].…”
mentioning
confidence: 99%